Efficient removal of hexavalent chromium from water by an adsorption–reduction mechanism with sandwiched nanocomposites. Issue 27 (23rd April 2018) - Liu, Weikang; Yang, Liang; Xu, Shihao; Chen, Yao; Liu, Bianhua; Li, Zhong; Jiang, Changlong
Abstract : A sandwiched nanocomposite has been developed to remove hexavalent chromium ion Cr(vi ) from water by an adsorption–reduction mechanism. Abstract : Hexavalent chromium Cr(vi ), one of the most toxic contaminants, is released in the environment due to various anthropogenic activities. This study presents a novel sandwiched nanocomposite synthesized using graphene oxide (GO), manganese dioxide (MnO2 ) nanowires, iron oxide (Fe3 O4 ) nanoparticles and polypyrrole (PPy) to remove hexavalent chromium ion Cr(vi ) from water by an adsorption–reduction mechanism. In the sandwiched nanocomposites, GO provided enough surface area, functional groups, and hydrophilic surface for efficient absorption. Fe3 O4 nanoparticles with excellent magnetic properties make it easy to separate and recover from water. Under acidic conditions, MnO2 nanowires act as both template and oxidant to initiate the polymerization of pyrrole monomers on its freshly activated surface to obtain GO/MnO2 /Fe3 O4 /PPy (designated as GMFP) nanocomposite. GMFP could effectively adsorb Cr(vi ) through electrostatic attraction, and the adsorbed Cr(vi ) ions were partly reduced to trivalent chromium Cr(iii ) (62%), resulting in the efficient adsorption and high removal of Cr(vi ) from water. Hexavalent chromium adsorption by GMFP is strongly pH dependent and the adsorption kinetics followed the pseudo-second-order model. The Langmuir isothermal model described the adsorption isotherm data well and the maximum adsorption capacity was up to 374.53 mg g −1 at pH 2.0. These experimental results suggested that GMFP had great potential as an economic and efficient adsorbent of hexavalent chromium from wastewater, which has huge application potential.